2018
DOI: 10.1530/erc-17-0355
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogen withdrawal syndrome (AAWS) in the treatment of patients with prostate cancer

Abstract: Antiandrogen withdrawal syndrome is an unpredictable event diagnosed in patients with hormone-sensitive prostate cancer treated with combined androgen blockade therapy. It is defined by prostate-specific antigen value reduction, occasionally associated with a radiological response, that occurs 4-6 weeks after first-generation antiandrogen therapy discontinuation. New-generation hormonal therapies, such as enzalutamide and abiraterone acetate, improved the overall survival in patients with metastatic castration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…We observed that low anti-androgen concentrations increased the proliferation rate of ResB cells (Fig. 1a) in medium supplemented with androgen containing normal FCS, suggesting an anti-androgen withdrawal effect in ResB but not ResA cells 33,34 . Interestingly, enzalutamide on its own did not induce AR activity (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…We observed that low anti-androgen concentrations increased the proliferation rate of ResB cells (Fig. 1a) in medium supplemented with androgen containing normal FCS, suggesting an anti-androgen withdrawal effect in ResB but not ResA cells 33,34 . Interestingly, enzalutamide on its own did not induce AR activity (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The antiandrogen withdrawal syndrome (AAWS) is defined as a further significant (>50%) reduction in PSA values after the discontinuation of antiandrogen therapy, which can be explained by AR mutations shifting the antiandrogen activity from antagonist to agonist. Several studies have reported AAWS after discontinuation of abiraterone or enzalutamide [110] , [111] , [112] . The second one is the L701H mutation that results in activation of the AR by glucocorticoids such as prednisone [113] .…”
Section: Therapeutic Resistance In Crpcmentioning
confidence: 99%
“…Some may attribute the objective responses seen in this patient after discontinuing the antiandrogen (bicalutamide) to antiandrogen withdrawal syndrome (AAWS). AAWS, usually defined as >50% decline in PSA following cessation of the antiandrogen, has been increasingly recognized and reviewed [9][10][11] . A large multi-institutional clinical trial (CALGB 9583) to investigate AAWS in androgen-independent prostate cancer patients (with a median age of 72 years) has shown that 11% of patients experienced AAWS with the median time to PSA progression at 5.9 months, and objective responses of measurable disease were observed in 2% of patients 12 .…”
Section: Discussionmentioning
confidence: 99%